Еврейская девушка для русского президента - Корш Вадим (Криминальный сюжет, 1997)
Экземпляры: ф.2 (2005) / Инвентарный номер: 48960 / Цена: / Сис.шифр: 84(5Изр)-4 / Авт.знак: К 70 / ГРНТИ: 17.82.31 / ББК: 84(5Изр)-44